Max Weber’s Outer World/Inner World and the Principe of Rationality (London Journal of Research In Humanities and Social Sciences, 2024)
Max Weber (1864-1920)revealed his major Sociological observation, of the Principle of Rationality. The Principle of Rationality consisted of two social movements, Substantive (traditional culture/inner world) and Formal Rationality (modern society, Money Economy(Outer world).
Keywords: trascendentperception; immanentperception; cognitive equilibrium; Community.; resources; Megalithism; reuse; multitemporality; Typhlotechnology; material adaptation; visual impairment